Somatostatin and Neuropeptide Y in Cerebrospinal Fluid: Correlations With Amyloid Peptides Aβ1–42 and Tau Proteins in Elderly Patients With Mild Cognitive Impairment - Duron, Emmanuelle; Vidal, Jean-Sébastien; Grousselle, Dominique; Gabelle, Audrey; Lehmann, Sylvain; Pasquier, Florence; Bombois, Stéphanie; Buée, Luc; Allinquant, Bernadette; Schraen-Maschke, Susanna; Baret, Christiane; Rigaud, Anne-Sophie; et al. (Frontiers in Aging Neuroscience, 2018)
A combination of low cerebrospinal fluid (CSF) Amyloid β 1-42 (Aß) and high Total-tau (T-Tau) and Phosphorylated-tau (P-Tau) occurs at a prodromal stage of Alzheimer’s disease (AD) and recent findings suggest that network abnormalities and interneurons dysfunction contribute to cognitive deficits. Somatostatin (SOM) and Neuropeptide Y (NPY) are two neuropeptides which are expressed in GABAergic interneurons with different fates in AD the former only being markedly affected. The aim of this study was to analyze CSF SOM, NPY and CSF Aβ 1-42; T-tau, P-tau relationships in 43 elderly mild cognitively impairment (MCI) participants from the BALTAZAR cohort. In these samples, CSF SOM and CSF Aβ on the one hand, and CSF NPY and CSF tau and P-tau on the other hand are positively correlated. CSF SOM and NPY concentrations should be further investigated to determine if they can stand for early AD biomarkers.